Formulating Self-Microemulsifying Drug Delivery Systems from Bay Leaves (Eugenia polyantha Wight) with Virgin Coconut Oil and Its Anti- Diabetic Activity: Anti-Diabetic Activity of Self-Microemulsifying Drug Delivery Systems from Bay Leaves - Prihapsara, Fea; Nur Artanti, Anif; Harini, Marti; Widiyani, Tetri; Zuhra Nazilla, Syahnidar; Widoninggar, Rengganis (Iranian Journal of Pharmaceutical Sciences, 2020)
Insulin resistance is a pathological condition associated with the inability of target tissues to insulin response. Bay leaf (Eugenia polyantha Wight) extract has been used for the treatment of insulin-resistant type-2 diabetes mellitus (IRDM), but it has low solubility and bioavailability. To overcome these problems, chloroform extract of bay leaves was formulated into a self-micro emulsifying drug delivery system (SMEDDS) using virgin coconut oil (VCO) as a carrier oil. This study aims to generate a micro-herbal medicine and to determine the effect of a micro-herbal, derived from bay leaves, as an anti-IRDM agent. Homogeneous formulations were evaluated for extract loading, emulsification time, size, size distribution, and the polydispersity index of the nano-emulsion droplets. In addition, their anti-IRDM activities were investigated on insulin-resistant rats using extracts, SMEDDS, metformin, negative control, and normal groups. Each group consisted of five randomly selected male Wistar rats. Blood cholesterol levels were measured at 0, 80, and 95 days. Data were analyzed by using ANOVA. The results showed that the optimum SMEDDS formula was tween 80: PEG 400: VCO (48%:32%:20%) in a total volume of 5 mL. It has less than 1-minute emulsification time with an average 141.4 μm of droplet size and 0.254 of polydispersity index. Morphological observation revealed that the microemulsion particles were spherical and stable in a variety of pH media. The hypoglycemic effects of singledose metformin, SMEDDS, and the combination of a half dose of SMEEDS with metformin were 28.3%, 15.6%, and 34.6%, respectively. The combination of a half dose of SMEDDS (91.75 mg/kg BW) and a half dose of metformin (22.5 mg/kg BW) provides the best anti-diabetic activity of bay leaves micro-herbal.